Impact of Frequent Administration of Bacteriophage on Therapeutic Efficacy in an A. baumannii Mouse Wound Infection Model - Rouse, Michael D.; Stanbro, Joshua; Roman, Jessica A.; Lipinski, Michelle A.; Jacobs, Anna; Biswas, Biswaijt; Regeimbal, James; Henry, Matthew; Stockelman, Michael G.; Simons, Mark P. (Frontiers in Microbiology, 2020)
The spread of multidrug antibiotic resistance is a widely recognized crisis in the treatment of bacterial infections. Recently, the World Health Organization published its first ever list of antibiotic-resistant "priority pathogens" – a catalogue of bacteria that pose as threats to human health with A. baumannii listed in the “Priority 1: Critical” category. With the increasing prevalence of antibiotic resistance and limited development of new classes of antibiotics, alternative antimicrobial therapies are needed, with lytic bacteriophage (phage) specifically targeted against each of the high priority bacterial infections as a potential approach currently in development towards regulatory approval for clinical use. Balb/c mice were prophylactically administered PBS or phage selected against A. baumannii strain AB5075. After 3 weeks, mice were anesthetized, wounded (dorsal) and challenged topically with AB5075. Following infection, mice were subsequently treated with PBS or phage for three consecutive days, and evaluated for 3 weeks to assess the safety and efficacy of the phage treatment relative to the control. We assessed mortality, bacterial burden, time to wound closure, cytokine profiles, host cellular immunity, and finally neutralizing antibodies. In our study, we found that prophylactic phage administration led to a significant reduction in monocyte-related cytokines in serum compared to mice given PBS. However, we detected no significant changes to circulating blood populations or immune cell populations of secondary lymphoid organs compared to PBS-treated mice. Following prophylactic phage administration, we detected a marked increase in total immunoglobulins in serum, particularly IgG2a and IgG2b. Furthermore, we determined that these antibodies were able to specifically target phage and effectively neutralize their ability lyse their respective target. In regards to their therapeutic efficacy, administration of phage treatment effectively decreased wound size of mice infected with AB5075 without adverse effects. In conclusion, our data demonstrate that phage can serve as a safe and effective novel therapeutic agent against A. baumannii without adverse reactions to the host and pre-exposure to phage does not seem to adversely affect therapeutic efficacy. This study is an important proof of concept to support the efforts to develop phage as a novel therapeutic product for treatment of complex bacterial wound infections.